2016
DOI: 10.1002/ece3.2060
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding and evaluation of genetic diversity in Cyprinidae fish in the midstream of the Yangtze River

Abstract: The Yangtze River is the longest river in China and is divided into upstream and mid‐downstream regions by the Three Gorges (the natural barriers of the Yangtze River), resulting in a complex distribution of fish. Dramatic changes to habitat environments may ultimately threaten fish survival; thus, it is necessary to evaluate the genetic diversity and propose protective measures. Species identification is the most significant task in many fields of biological research and in conservation efforts. DNA barcoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
52
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 45 publications
6
52
2
2
Order By: Relevance
“…The success rates of DNA barcoding approach in our study (95.60%) was higher than the 93% success rate reported for Canadian freshwater fish (Hubert et al., ) and the 90% success rate reported for North American freshwater fish (April, Mayden, Hanner, & Bernatchez, ). However, our DNA barcoding success rate was lower when compared to 100% success rate reported by Shen, Guan, Wang, and Gan () and 98.30% success rate reported for Indian freshwater fishes (Lakra et al., ). In most cases, our study shows that COI sequences effectively clustered most of the conspecific and congeneric species.…”
Section: Discussioncontrasting
confidence: 80%
“…The success rates of DNA barcoding approach in our study (95.60%) was higher than the 93% success rate reported for Canadian freshwater fish (Hubert et al., ) and the 90% success rate reported for North American freshwater fish (April, Mayden, Hanner, & Bernatchez, ). However, our DNA barcoding success rate was lower when compared to 100% success rate reported by Shen, Guan, Wang, and Gan () and 98.30% success rate reported for Indian freshwater fishes (Lakra et al., ). In most cases, our study shows that COI sequences effectively clustered most of the conspecific and congeneric species.…”
Section: Discussioncontrasting
confidence: 80%
“…Since the launch of an international campaign to DNA barcode the c.a. 33,900 fish species (FISHBOL, (Ward, Hanner, & Hebert, )), the effectiveness of DNA barcoding to identify fish species is increasingly acknowledged (April, Mayden, Hanner & Bernatchez L, ; Dahruddin, Hutama, & Busson, ; Durand et al, ; Geiger et al, ; Hubert et al, ; Kadarusman & Hadiaty, ; Knebelsberger et al, ; Pereira, Hanner, Foresti, & Oliveira, ; Randall & Victor, ; Shen, Guan, et al, ; Shen, Kang, et al, ; Victor, Valdez‐Moreno, & Vásquez‐Yeomans, ; Ward, Zemlak, Innes, Last, & Hebert, ; Weigt, Baldwin, & Driskell, ; Winterbottom et al, ). Maximum intraspecific genetic distances are usually lower than the distances to the nearest phylogenetic relative, and large‐scale assessment previously reported that this barcode gap is observed for nearly 90 per cent of the species examined for well‐known ichthyofauna (April, Mayden, Hanner, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other overlooked taxa may be distinguished by DNA barcode divergences of 0.7%–3.8% within nine morphospecies present in a single province. The contribution of DNA barcoding for the detection of new taxa was acknowledged in most DNA barcoding campaigns focusing on large river basins (Decru et al, ; Hubert et al, ; Nascimento et al, ; Pereira, Pazian, Hanner, Foresti, & Oliveira, ; Shen, Guan, Wang, & Gan, ). Multiple lineages were suspected within Enteromius miolepis on the basis of DNA barcodes.…”
Section: Discussionmentioning
confidence: 99%